Tackling risk factors for type 2 diabetes in adolescents: PRE-STARt study in Euskadi - Elena Alustiza; Amaia Perales; Maider Mateo-Abad; Irene Ozcoidi; Garbiñe Aizpuru; Olatz Albaina; Itziar Vergara (Elsevier, 2021)
Introduction: Obesity in the child population and its effect in the development of metabolic diseases are a public health issue. One of the aims of the European Project in a health system, is the evaluation of the effectiveness of a multidisciplinary health promotion program directed at adolescents with risk factors associated with the development of type 2 Diabetes Mellitus (T2DM). Patients and methods: Randomised clinical trial with two groups of 12-14 year-old overweight adolescents. The intervention group took part in a multidisciplinary program for 24 months. This program was based on 11 group sessions (8 main sessions and 3 additional support ones) for adolescents and their guardians. The control group received usual care at primary care level. Longitudinal regression models were adjusted to assess the evolution of anthropometric measures and living habits at baseline, 3, 6, 12, and 24 months in both groups. Results: There were 92 participants, equally distributed by group. Statistically significant differences were observed between intervention and control groups in several results: evolution of the body mass index; increase in the consumption of fruits and vegetables; decrease in the consumption of snacks and sweetened drinks; and increase in the number of days per week with more than one hour of physical activity. Conclusions: The results confirm the effectiveness of this multidisciplinary program, both in the evolution of the body mass index, and in the improvement of the eating and physical activity habits, all of them risk factors for the future development of metabolic diseases, such as T2DM. Resumen: Introducción: La obesidad en la población pediátrica y su efecto en la génesis de enfermedades metabólicas, constituye un gran problema de salud pública. Uno de los objetivos del estudio de ámbito europeo en un sistema de salud es evaluar la efectividad de un programa de promoción de la salud dirigido a adolescentes con factores de riesgo asociados al desarrollo de Diabetes Mellitus tipo 2 (DMT2). Pacientes y métodos: Ensayo clínico con doble grupo aleatorizado de adolescentes de 12 a 14 años con exceso ponderal. El grupo intervención recibió un programa multidisciplinar durante 24 meses, de 11 sesiones grupales (8 al inicio, 3 de refuerzo) junto a sus tutores. El grupo control continuó el seguimiento habitual por los equipos de pediatría de Atención Primaria. Se plantean modelos longitudinales para estudiar la evolución de medidas antropométricas y hábitos de vida desde el momento basal, a los 3, 6, 12 y 24 meses. Resultados: Participaron 92 personas en el estudio, igualmente distribuidas por grupo. Se observaron mejoras estadísticamente significativas en varios resultados: evolución del índice de masa corporal; aumento del consumo de frutas y verduras; disminución del consumo de snacks y de bebidas azucaradas; y aumento del número de días por semana en los que realizan más de 1 hora de ejercicio físico. Conclusiones: Los resultados confirman la efectividad del programa multidisciplinar tanto en la evolución del índice de masa corporal como en la mejora de los hábitos alimentarios y de actividad física, todos ellos factores de riesgo en la génesis de enfermedades metabólicas futuras, como la DMT2.